Exploring Argumentation Performance in Constructing English Academic Text of EFL University Students in Indonesia - Hanna Sundari; Juhana Juhana; Widya Rizky Pratiwi (Fakultas Ilmu Pendidikan dan Humaniora (FIPH), Universitas Muhammadiyah Semarang, 2026)
Research proposals (RP) require concurrence of clarity, logic, and persuasive arguments in presenting knowledge and justifying research. However, lack of comprehensive research on argumentation performance presented in RPs and the influential factors in argument development. To fill the gap, this research involved thirty-one EFL university-students in Indonesia through a questionnaire, textual analysis of the RPs, and semi-structured interview. This study reveals a diverse range of argumentation performances when constructing RPs. Most students demonstrated competent argumentation performance with clear claims and evidence, a smaller number struggled with in-depth analysis. Cognitive/metacognitive process and communicative competence with critical thinking emerged as key strengths, but areas like enculturation practicing and reasoning require further development. Interview data highlighted the interconnectedness of academic knowledge, cognitive abilities, and personal factors in shaping argumentation skills.